Comportamento de arara-azul-de-lear (Anodorhynchus leari, Bonaparte, 1856) em cativeiro e a influência da técnica flocking na interação de pares - Favoretto, Gabriela Rodrigues (2016)
The Lear's Macaw (Anodorhyncus leari) is an endemic parrot of northeastern Bahia state, classified as endangered mainly due to the destruction of their habitats and wildlife trade. It was recently discovered in the wild, and few studies are known for this species. Understanding behavioral patterns of species threatened by extinction is essential for developing effective conservation strategies. Here we describe the behavioral repertoire of a group of this species maintained by the São Paulo Zoological Park Foundation. We carried out observations between October 2014 and February 2015, totaling 348 hours of sampling effort through ad libitum continuous record, in two different environmental conditions, both in in pairs and in flock. We described 60 behavioral states, grouped in categories maintenance, locomotion, feeding, social, stereotyped, reproductive and alert. We also found five patterns of vocalization (alarm, contact, cohesion, reproduction and imitation). Most of the behaviors described for other species is also reported here to A. leari, more similar to A. hyacinthinus. We discuss the differences in order to contribute to the formulation of a behavioral profile for this species, and with information that may assist in maintaining normal behavior in captivity.